Features and challenges of the modern labor market - G. N. Ryazanova (Управление)
In recent decades, there has been a dynamic transformation of the socio-economic eco-system, in general and its components in particular. Cardinal changes in the values and motives of economic decisions, the compression of the time continuum of the life cycle of products and enterprises are reflected in the financial and resource market derived from the commodity market. The employer-employee relationship is changing, there are more disagreements, since the requirements of the organization and the expectations of the applicant often differ significantly. Modern employers do not have enough professional competencies of employees, it is important to combine a range of knowledge, skills and personal qualities. The author of this article presents the features of the modern labor market, the results of employers’ research on the demand for specialists. The work methodology is based on scientific research methods of cognition, such as statistical and comparative analyzes, questionnaires and the method of expert assessments, a systematic approach. The study reveals the indispensability of such employees’ qualities as scale and critical thinking, a high level of stress tolerance, the ability to combine the roles of a leader and a team member depending on the task, skills for evaluating large information arrays and digital competencies. The conclusion is formulated about the need for applicants to strengthen not only hard skills, but also to constantly develop soft skills to compete against the challenges of the labor market.